Advance care planning and advance directive awareness among East Asian older adults: Japan, Hong Kong and South Korea. Issue 1 (20th November 2020) - Kawakami, Aki; Kwong, Enid WY; Lai, Claudia KY; Song, Mi Sook; Boo, Sunjoo; Yamamoto‐Mitani, Noriko
Abstract : Aim: Population aging is a global phenomenon, and East Asian countries are no exception. However, the use of advance care planning (ACP) and advance directives (ADs) are not widespread in East Asia. This study aimed to examine the awareness of ACP/ADs and its related factors among community‐dwelling older persons in Japan, Hong Kong and South Korea. Methods: This was a cross‐sectional, cross‐cultural questionnaire conducted among a convenience sample of community‐dwelling persons. The questionnaire included information regarding awareness of ACP/ADs and personal information. Multiple logistic regression was used assess relationships between awareness of ACP/ADs and potential related factors. Results: The sample consisted of 404 community‐dwelling older adults: 174 (43.0%) from Japan, 132 (32.7%) from Hong Kong and 98 (24.3%) from South Korea. In total, 122 participants (30.2%) had heard of ACP/ADs. Multiple logistic regression analysis revealed that an educational level >12 years was significantly associated with increased ACP/ADs awareness (adjusted odds ratio [AOR]: 2.19, 95% confidence interval (CI): 1.18–4.07, P = 0.01). The rate of those who have heard of ACP/ADs was significantly higher among Japanese than South Koreans were (AOR: 4.54, 95% CI: 1.64–12.58, P  < 0.01), those from Hong Kong than South Korea (AOR: 5.15, 95% CI 1.89–14.0, P  < 0.01) after some variables with significant differences among the three countries were controlled. Conclusions: In particular, support tailored to the targets' educational levels will be required. It is also suggested that support is needed to enhance awareness of ACP/ADs in East Asia, although there is a difference in degree of awareness among the three countries. Geriatr Gerontol Int 2021; 21: 71–76 .